Gambaran Kadar Kreatinin Serum Dan Lama Rawatan Pada Pasien Gagal Jantung Kongestif di RSUD Arifin Achmad Provinsi Riau Januari 2012 - Desember 2014 - Dyah Siswanti E; Fatmawati Fatmawati; M. Ikhsanul Fikri (Fakultas Kedokteran Universitas Riau, 2016)
Worsening renal function in patient with congestive heart failure affect the length of hospital stay. The purpose of thisstudy was to describe the creatinine serum levels and the length of hospital stay in patient with congestive heartfailure treated in Arifin Achmad hospital Riau Province January 2012 – December 2014. This study was done withcross sectional approach. This study found the most common creatinine serum levels found were <1.5 mg/dl (73.2%)with an average of 1.30 mg/dl and the range was 0.10 – 6.63 mg/dl. The value of left ventricular ejection fraction withan average of 44.9% and the range was 12% - 79%. Length of hospital stay in patients were >5 days commonly withan average of 7.29 days and the range was 1 – 29 days. The result of this study showed that the possibility ofcreatinine serum levels is not the only one predictor to determine the length of hospital stay in patient with congestiveheart failure.